Can teacher‐centered community‐based conservation programs influence student household sustainable behaviors near a biodiversity hotspot? - Corinne J. Kendall; Sarah J. Carrier; Elizabeth Folta; John Tinka; Aimee Fraulo; Austin Leeds; Kristen E. Lukas (Conservation Science and Practice, 2022)
Abstract Local communities living on the borders of protected areas can be key drivers of environmental degradation. Community‐based conservation initiatives seek to use sustainable activities as a strategy for mitigating these degradative behaviors while improving livelihoods but must be scalable to the site and sustainable over time. Teacher training, as a means of information transfer to the broader community, is one technique for implementing long‐term sustainable behavior programs. To be effective, sustainability practices must reach beyond behavior change in teachers to influence students and the broader community in which they work. UNITE for the Environment (UNITE) is a community‐based environmental sustainability program located along the border of Kibale National Park in Uganda, a site of high biodiversity, particularly for primates. UNITE focuses on conducting teacher trainings with 12 schools within 5 km of the park. We conducted an evaluation of the effectiveness of the transfer of UNITE's sustainability practices to the broader community. Families of teachers and students from schools that UNITE worked with, as well as control schools, were surveyed to assess their use of sustainable activities promoted by UNITE. Sustainable activities included specific agricultural practices, composting, bee‐keeping and fuel‐efficient stoves, while controlling for possible confounding variables between households including socioeconomic, spatial, and demographic variables. Results revealed that UNITE households, in comparison with control group households, showed greater use of sustainable practices for 12 of 13 behaviors tested. Wealth was the most influential of socioeconomic factors, with wealthier individuals more likely to implement sustainable activities. UNITE participants had greater value of the environment and belief in their ability to affect the environment than members of the control group. This study demonstrates the ability of teacher training programs to influence sustainable behavior, even while controlling for socioeconomic factors, suggesting that other programs should consider this approach to community‐based conservation.